Endovascular treatment of very small intracranial aneurysms: Clinical article - Ioannidis, I; Lalloo, S; Corkill, R; Kuker, W; Byrne, J (2010)
Object. Endovascular treatment of very small aneurysms poses a significant technical challenge for endovascular therapists. The authors review their experience with a series of patients who had intracranial aneurysms smaller than 3 mm in diameter. Methods. Between 1995 and 2006, 97 very small aneurysms (defined for purposes of this study as < 3 mm in diameter) were diagnosed in 94 patients who were subsequently referred for endovascular treatment. All patients presented after subarachnoid hemorrhage, which was attributed to the very small aneurysms in 85 patients. The authors reviewed the endovascular treatment, the clinical and angiographic results of the embolization, and the complications. Results. Five (5.2%) of the 97 endovascular procedures failed, and these patients underwent craniotomy and clip ligation. Of the 92 aneurysms successfully treated by coil embolization, 64 (69.6%) were completely occluded and 28 (30.4%) showed minor residual filling or neck remnants on the immediate postembolization angiogram. Complications occurred in 7 (7.2%) of 97 procedures during the treatment (3 thromboembolic events [3.1%] and 4 intraprocedural ruptures [4.1%]). Seventy-six patients were followed up angiographically; 4 (5.3%) of these 76 showed angiographic evidence of recanalization that required retreatment. The clinical outcomes for the 76 patients were also graded using the Glasgow Outcome Scale. In 61 (80.3%) cases the outcomes were graded 4 or 5, whereas in 15 (19.7%) they were graded 3. Seven patients (7.4%) died (GOS Grade 1), 2 due to procedure-related complications (intraoperative rupture) and 5 due to complications related to the presenting subarachnoid hemorrhage. Conclusions. Endosaccular coil embolization of very small aneurysms is associated with relatively high rates of intraprocedural rupture, especially intraoperative rupture. With the advent of more sophisticated endovascular materials (microcatheters and microguidewires, soft and ultrasoft coils, and stents) endovascular procedures have become feasible and can lead to a good angiographic outcome.